The politics of actually existing unsustainability human flourishing in a climate-changed, carbon constrained world - Barry, John Vincent 1903-1969 (Oxford University Press, 2012)
"Going against both the naive techno-optimism of 'greening business as usual' and a resurgent 'catastrophism' within green thinking and politics, The Politics of Unsustainability offers an analysis of the causes of unsustainability and diminished human flourishing. It makes a case for seeing that it is profound and deepening unsustainability and growing injustice that characterises the modern world, and that therefore the focus of green or other progressive thinking should shift from its current framing in terms of 'sustainability', 'sustainable development', and 'theories of justice'. The book locates the causes of unsustainability in dominant capitalist modes of production, debt-based consumer culture, the imperative for orthodox economic growth, and the dominant ideology of neo-classical economics.
Machine generated contents note: -- Preface and Acknowledgements -- 1. Introduction -- 2. Vulnerability -- 3. Resilience, Transition and Creative Adaptability -- 4. A critique of neo-classical economics as a regime of 'truth': empire and emperors with no clothes -- 5. Green Political Economy I: Sufficiency and Security -- 6. Green Political Economy II: Solidarity and Sharing -- 7. Greening Civic Republicanism I -- 8. Greening Civic Republicanism II: Sustainability Service, a Green Republican Economy and Agonistic Politics -- 9. Conclusion: Dissident thinking in Turbulent Times
Keywords: Economic development; Economic security; Green movement; POLITICAL SCIENCE / Public Policy / Environmental Policy; Wirtschaftsentwicklung; Umweltökonomie; Umweltpolitik; Nachhaltigkeit